Effect of vitamin D on muscle function and injury in elite adolescent dancers: a randomized double-blind study - Wyon, M. A.; Wolman, R.; Kolokythas, N.; Sheriff, K.; Galloway, S.; Mattiussi, A. (International Journal of Sports Physiology and Performance, 2019)
Purpose: A number of studies have noted low levels of vitamin D in dancers, and this has been associated with increased risk of injuries and decreased muscle-strength indices. The aim of the present study was to examine whether vitamin D supplementation over a 4-mo period can improve muscle function and injury incidence. Methods: A total of 84 participants volunteered; exclusion criteria and dropout (19%) reduced the cohort to 67 participants (females = 29 and males = 38; 17-19 y). Participants were randomly assigned to either an intervention or placebo group (2:1 ratio). All provided a venous blood sample before and after the 4-mo study period. The intervention group received 120,000 IU vitamin D to be taken over a 1-wk period, and the placebo group received the same number of inert pills. Participants completed a series of muscle function tests before and after the monitoring period. Injury incidence was recorded by the independent health team at the school. Results: Preintervention, 6% of the cohort were vitamin D deficient, 81% were insufficient, and 13% had sufficient levels; postintervention, 53% were insufficient and 47% were sufficient. The intervention group reported a significant increase in serum 25(OH)D3 (57%; P < .00) and isometric strength (7.8%; P = .022) but not muscle power. There was a significant association between traumatic injury occurrence for the intervention and control groups (10.9% vs 31.8%; P < .02). Conclusion: Vitamin D supplementation decreased the numbers of deficient and insufficient participants in this cohort. The intervention group reported a small significant increase in muscle strength that was negatively associated with traumatic injury occurrence.